In pursuit of the African PhD: A critical survey of emergent policy issues in select sub-Saharan African nations, Ethiopia, Ghana and South Africa. (September 2016) - Molla, Tebeje; Cuthbert, Denise
After decades of decline, African higher education is now arguably in a new era of revival. With the prevalence of knowledge economy discourse, national governments in Africa and their development partners have increasingly aligned higher education with poverty reduction plans and strategies. Research capacity has become a critical development issue; and widening participation to doctoral education is seen as an instrument for enhancing this capacity. Against this backdrop, this paper presents a review of emerging initiatives and policies that have some bearing on the PhD in select sub-Saharan African nations, namely Ethiopia, Ghana and South Africa. The findings show a shared optimism about the economic value of higher education, and explicate divergences and convergences in the framing of problems and policy responses related to doctoral education across the three nations. In the conclusion we reflect on challenges and policy omissions in the pursuit of the African PhD.